Genetic Insights Into the Introduction History of Black Rats Into the Eastern Indian Ocean - Thomson, Vicki A.; Wiewel, Andrew S.; Palmer, Russell; Hamilton, Neil; Algar, Dave; Pink, Caitlyn; Mills, Harriet; Aplin, Ken P.; Clark, Geoffrey; Anderson, Atholl; Herrera, Michael B.; Myers, Steven; et al. (Frontiers in Ecology and Evolution, 2022)
Islands can be powerful demonstrations of how destructive invasive species can be on endemic faunas and insular ecologies. Oceanic islands in the eastern Indian Ocean have suffered dramatically from the impact of one of the world’s most destructive invasive species, the black rat, causing the loss of endemic terrestrial mammals and ongoing threats to ground-nesting birds. We use molecular genetic methods on both ancient and modern samples to establish the origins and minimum invasion frequencies of black rats on Christmas Island and the Cocos-Keeling Islands. We find that each island group had multiple incursions of black rats from diverse geographic and phylogenetic sources. Furthermore, contemporary black rat populations on these islands are highly admixed to the point of potentially obscuring their geographic sources. These hybridisation events between black rat taxa also pose potential dangers to human populations on the islands from novel disease risks. Threats of ongoing introductions from yet additional geographic sources is highlighted by genetic identifications of black rats found on ships, which provides insight into how recent ship-borne human smuggling activity to Christmas Island can negatively impact its endemic species.